Pedagogy and Institutional Values: The Social Capital that Underpins Socially Constructivist Pedagogy and the Common Good - Campbell, James (INTI International College, 2009)
The analysis of Syed Hussein Alatas, provides us with a basic framework from which to engage the way creativity and change can be articulated in education without slipping into a neo-colonial mindset. The core binary that Alatas presents us is between the 'captive' mind and the 'creative' mind. Contemporary Malaysian educational literature recognises that the demands of the knowledge economy and globalization necessitate engaging with socially constructivist pedagogy as a way of addressing the limitations and narrowess of what are referred to as traditional authoritarian 'top down' teaching methods. However this retheorization of pedagogical practice needs to be approached in a fashion that recognises and respects local values and culture. The social values and capital that inform pedagogy both in its formal level as officially sanctioned techniques but also in its informal level as the implicit practices that characterise human interaction on campus require a much closer look at the relationship between pedagogy, social structure and social values. The clear yet very deep insight of Syed Hussein Alatas, on the importance of the creative mind as an alternative to captivity provides us with a Malaysian theorization that is both local but also global and relevant to how we understand reform and education in the higher education sector.